Rethinking Initial Teacher Training from a Socioemotional Dimension - Lagos San Martín, Nelly Gromiria (2020)
This study reflects on Teacher Training within a context of profound social change and transformation which challenges initial teacher training and pedagogical endeavors. Teacher Training must be reevaluated and better aligned to such changes where self-awareness, self-management, awareness of the other, social skills and responsible decision-making must be valued as acquired skills that cannot be taught. Teachers should be able to integrate both knowledge and values within the socially constructed context where they teach and, at times, ridden with inequalities, economic constraints and social vulnerabilities. Their role is, decidedly, one as mediator of knowledge and a student appropriation process of that knowledge and for which further discussion is required to better understand this concept.